2014
DOI: 10.1002/oby.20659
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of food perception: Coordinate-based meta-analyses of neuroimaging studies in multiple modalities

Abstract: Objective The purpose of this study was to compare the results of the three food-cue paradigms most commonly used for functional neuroimaging studies to determine: i) commonalities and differences in the neural response patterns by paradigm; and, ii) the relative robustness and reliability of responses to each paradigm. Design and Methods functional magnetic resonance imaging (fMRI) studies using standardized stereotactic coordinates to report brain responses to food cues were identified using on-line databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 41 publications
5
110
0
Order By: Relevance
“…Further, as compared to healthy subjects, individuals with eating disorders, obesity, or elevated propensity for weight gain showed less of a drop in food cue responses in sated vs. hungry states (Huerta et al, 2014; Sun et al, 2015). These studies report average activity across many neurons.…”
Section: Discussionmentioning
confidence: 93%
“…Further, as compared to healthy subjects, individuals with eating disorders, obesity, or elevated propensity for weight gain showed less of a drop in food cue responses in sated vs. hungry states (Huerta et al, 2014; Sun et al, 2015). These studies report average activity across many neurons.…”
Section: Discussionmentioning
confidence: 93%
“…A coordinatebased meta-analysis of neuroimaging studies contrasting food tastes with tasteless solutions, confirmed insular areas as location of primary gustatory cortex. In addition, specific areas in cingulate, parahippocampal, postcentral, medio frontal and precentral gyrus, as well as caudate, claustrum, thalamus, and lentiform nucleus were found to be involved in taste processing [31]. Processing of individual taste qualities seemed to be relatively restricted to specific areas in the gustatory cortex although some anatomical overlapping exists.…”
Section: Discussionmentioning
confidence: 96%
“…Trait-like dimensions of appetite were related to the contrast in brain activation from cues of high-ED foods -low-ED foods. Enjoyment-of-food scores were negatively related to activation in the anterior insula [i.e., the primary taste cortex (47)], which is a brain region that has been implicated in cognition (53) and is commonly responsive to both food tastes and images (54). Similarly, food-responsiveness scores were negatively related to activation in the declive, which is part of the posterior cerebellum that is involved in cognitive processing (55) with previous associations to food cues in adults (42) and adolescents (56).…”
Section: Discussionmentioning
confidence: 99%